In the court of the Pear King : French culture and the rise of realism - Petrey, Sandy (Cornell University Press, 2005)
"The period 1830-1832 witnessed a remarkable series of cultural and political milestones in France. In 1830, a revolution overturned one monarchy, only to replace it with another. In 1831, Charles Philippon's caricature of Louis-Philippe, the new monarch, as a pear achieved extraordinary popularity. Drawn on walls from one end of France to another, the pear caricature became a national obsession. In that same year, George Sand moved from the provinces to Paris and challenged gender stereotypes by adopting men's clothes and writing fiction in a man's voice. During 1830-1832, Stendhal and Balzac developed the techniques of the realist novel that still dominate much of the world's fiction.